Identification of polluted sites in four major rivers in Kuantan, Malaysia based on water chemistry estimates of aquatic microbial activity - Kozaki, D.; Norhasmira Idayu, Harun; Chong, C. H.; Murni Hayati, Esraruddin; Nor Atiah, Yunus; Aini Syazana, Derahman; Pu, Kee Seng; Nurul Syazwani, Alias; Kumutharani, Annamalai; Sarmila, Nagappan; Mohd Hasbi, Ab. Rahim; M. M., Yusoff (MDPI, 2019)
Kuantan in Pahang, Malaysia has experienced rapid development and environmental degradation over the past decade following the implementation of The National Physical Plan 2005. To assess water quality and identify polluted areas in the region, we measured the water chemistry and microbial activity in response to land-use changes for four major rivers, namely, Pahang, Kuantan, Belat, and Galing, using data from ion chromatography and portable water quality monitoring devices. The following were concluded: (1) significant differences in chemical oxygen demand, COD concentration among all monitored rivers suggest that COD and its associated biological reactions are key parameters to assess anthropogenic water quality degradation in our study area; (2) due to the low anthropogenic wastewater pollution, the dominant microbial reactions in the Pahang, Kuantan, and Belat rivers were aerobic microbial oxidation of organic compounds and nitrification by nitrifying bacteria, allowing the rivers to self-purify; (3) the Galing River predominantly experiences anaerobic decomposition of organic compounds through microbial denitrification and sulfate reduction due to the heavy anthropogenic land use in the river basin; and (4) the western side of the Galing River and upstream sites located within the industrial and business/servicing areas in the Kuantan city center experience the heaviest pollution.